Thái độ đối với thương hiệu và thái độ đối với quảng cáo sử dụng hình ảnh hấp dẫn giới tính qua một nghiên cứu thử nghiệm - Hà Minh, Trang; Trần Đăng, Khoa; Cao Quốc, Việt (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The use of sexual appeal in advertising is increasingly common in Vietnam and the world However, the role, effectiveness, and negative influence of sexual advertising on the brand have still been debatable points This study examines the relationship among feminist attitudes, ethical judgment, attitude toward the sexual advertising, and brand attitude We study three experimental groups through their judgement about three advertising video clips of three brands with various levels of women's sexual images The results show that: (i) Feminist attitudes affect positively attitude toward the sexual advertising; and (ii) attitude toward the sexual advertising plays a mediating role in the relationship among feminist attitudes, ethical judgment, and attitude toward the brand This investigation helps marketing managers to predict and manage the risks from using sexual advertising in Vietnam to the brand
Keywords: Brand; Brand attitude; Attitude toward advertising; Sexual appeal; Feminist attitude; Ethical judgment